Bridging the Gap: Women’s Evolving Role in Nuclear Science - Sitara Noor (CISS Insight Journal, 2025)
Nuclear science has played a transformative role in shaping societies, policies, and technologies for over a century. As the world turns to nuclear energy as a key solution to climate change and sustainable development, the nuclear sector should embrace an innovative, diverse, and inclusive workforce. The trailblazing journeys of pioneering women in nuclear science offer a powerful context for understanding women as bridge builders in a historically male-dominated field. Their groundbreaking work in nuclear and medical physics laid the foundations for modern innovations. While highlighting the contributions of pioneering female figures, this study aims to shed light on the structural dynamics that continue to influence women’s participation in the nuclear sector. The paper also offers a way forward to promote inclusivity and equity through proposed changes at the grassroots level.